2013
DOI: 10.1111/acem.12039
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Research: Using Exception from Informed Consent, Evaluation of Community Consultations

Abstract: Background: In 1996, the U.S. Food and Drug Administration approved regulations authorizing an exception from informed consent (EFIC) for research conducted in emergency settings when obtaining prospective informed consent is not possible due to the potential subject's critical illness or injury. The regulations require that investigators conduct community consultation (CC) efforts before initiating a study and require that institutional review boards review the results of CC prior to approving a study. Howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 10 publications
2
22
0
Order By: Relevance
“…Ramsey and colleagues suggest involving "community advocates for research" (CARs) in the community consultation process-people who are viewed as leaders in communities or groups where outreach may be otherwise limited. 6 The TBI study did not implement this strategy, though having representatives from communities at high risk of TBI or where response rate was expected to be low may have been beneficial. Significantly more women and persons over the age of 65 provided feedback to researchers than what was expected according to service area demographics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ramsey and colleagues suggest involving "community advocates for research" (CARs) in the community consultation process-people who are viewed as leaders in communities or groups where outreach may be otherwise limited. 6 The TBI study did not implement this strategy, though having representatives from communities at high risk of TBI or where response rate was expected to be low may have been beneficial. Significantly more women and persons over the age of 65 provided feedback to researchers than what was expected according to service area demographics.…”
Section: Discussionmentioning
confidence: 99%
“…5,6 As such, it can be difficult to perform rigorous comparisons to other studies where community consultation took place. However, in published reports of community consultation and the TBI study, we see three themes around which feedback questions are often focused: support for the research, willingness to participate, and informational or meeting-specific satisfaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the UK, an amendment has been made to the European Union Clinical Trials Directive (2006) to allow research without consent in emergency situations through approval from ethics committees (Department of Health, United Kingdom 2006). In the US, post-implementation of the regulations for exception from informed consent (EFIC) using community consultation demonstrated high levels of satisfaction and trust in physicianinvestigators as indicated by surveys (Govindarajan et al 2013).…”
Section: Ethical Issues In Conducting Emergency Researchmentioning
confidence: 99%
“…In this issue of Academic Emergency Medicine, Govindarajan et al 10 describe the responses given by participants of CC activities when they were asked what they thought about the CC process. They were also asked what they learned about EFIC and a proposed EFIC study, RAMPART.…”
mentioning
confidence: 99%